Revision of the genus Didymocystis and the erection of the genus Didymosulcus gen. nov. (Trematoda, Didymozoidae) - Pozdnyakov, S. E. (Zoologicheskiĭ Zhurnal, 1990)
Didymocystis is revised and emended. Three genera described by Yamaguti in 1970 - Coeliodidymocystis, Didymocystoides and Univitellodidymocystis are synonymized with Didymocystis. The type species is D. reniformis and the genus now also contains D. acanthocybii, D. alolongae, D. opercularis, D. semiglobularis, D. submentalis and the new combinations D. scomberomori D. singularis, D. buccalis, D. exiguus, D. intestinomuscularis, D. oesophagicola, D. pectoralis, D. pinnicola, D. bifasciatus, D. sphyraenae and D. visakhapatnamensis. Didymosulcus gen. nov. is erected for species with a median groove on the posterior section of the body; the type species is D. katsuwonicola comb. nov. (for Didymocystis katsuwonicola) from Thunnus obesus and T. albacares in the Pacific. The new genus contains 2 new species and the following new combinations: Didymosulcus lanceolata, D. macrorchis, D. bifurcata, D. irregularis, D. nasalis, D. orbitalis, D. palati, D. philobranchia, D. philobranchiarca, D. poonui, D. spirocauda, D. superpalati and D. rotunditestis. D. aahi sp. nov. from the gill bars of T. alalunga and T. albacares in waters of the south-eastern Pacific is characterized by the shape of the body (anterior part of the body elongated, posterior part sharply curved) and an ovary which is directed forwards into one of the lateral lobes. D. dimidiatus sp. nov., from the upper palate of T. alalunga in the southern subtropical part of the Pacific, is characterized by body shape, which has a deep median groove, and the topography of internal organs. In body shape it is most similar to D. spirocauda from which it differs in the absence of a pharynx and of glandular cells around the base of the oesophagus and in having an ovary with 2 branches but no secondary branching. Didymozoon thynni, Didymocystis wedli Ariola 1902, D. bilobata and D. soleiformis are considered species inquirendae.